Corrosive injury to Esophagus: A ruinous curse to the affected patients (Bangladesh Journal of Medicine, 2025)
Background: Corrosive, a harmful chemical substance, causes devastating tissue injury when contacts with body surface or ingested, is a common cause of poisoning in developing world. Prevention and early initiation of therapy after ingestion can reduce the morbidity and mortality. The aim of the study was to evaluate the demographic features, clinical presentations, endoscopic findings, complications, and the outcome of esophageal injury in corrosive ingestion. Methods: The cross- sectional study followed by prospective observation was carried out from 05/08/2019 and 15/03/ 2022 in the Department of Gastroenterology in Sir Salimullah Medical College Mitford Hospital. Results: Our study showed that from 105 patients, the dominating patients were female [n = 75 patients (71.4 %), p < 0.001] and significant number of the patients 84 (80%) were unemployed [p < 0.001]. In this series 37 (35.2%), 40 (38.1%) and 14 (13.3%) were students, housewives and service holders respectively. Of these only one (1%) and five (4.8%) were illiterate and graduate respectively. Most of the patients had monthly income £20,000 BDT [n = 81 (77.1%), p < 0.001] and total 91 (86.7%) cases were suicidal and 11 (10.5%) were accidental ingestion of corrosive [p < 0.001]. The most common ingested corrosive in our series was Harpic 91 (86.7%) [p < 0.001]. Most common clinical feature was dysphagia 72.4% (n=76). Endoscopy of upper GIT revealed injury 55 (52.4%) and 44 (41.9%) in esophagus and stomach respectively with significant difference of finding with age (p < 0.05). Follow up endoscopy showed 13.3%(n=14) patients developed complication like esophageal stricture and gastric outlet obstruction and significant number of patients [n=91(86.7%)] didn’t develop any complication. Out of these 14 patients 57.1%(n=8) were managed by esophageal dilatation and 42.9%(n=6) were referred to surgery. Conclusion: Corrosive poisoning is a predominant and preventable condition in the developing countries. Preventive strategies should include regulation and packaging of corrosive substances, effective awareness program and strict legal action, decent psychosocial support system and counselling and proper education.Bangladesh J Medicine 2025; 36(2): 123-129